A Split-Face Comparative Study in Efficacy and Safety between the Combination of 4% Niacinamide and 4% Kojic Acid Cream versus 4% Hydroquinone Cream for Epidermal Melasma - Hindritiani, Reti; Nazlia, Felly; Octavia, Nadia; Rizqandaru, Trustia; Puspitosari, Diah; Ruchiatan, Kartika (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Melasma is a hyperpigmentation disorder that affects the quality of life, especially in women. Hydroquinone has remained the mainstay of melasma treatment. However, its safety for long-term usage became a great concern. Combination therapy, such as niacinamide and kojic acid, can be used as an alternative melasma treatment due to different mechanisms of action and synergism. Purpose: The aim of this study was to compare the efficacy and safety of a combination of 4% niacinamide and 4% kojic acid (N-K) vs. 4% hydroquinone (HQ) in epidermal melasma. Methods: This was a randomized, double blind, clinical study on 13 female epidermal melasma patients at the Cosmetic Dermatology Outpatient Clinic of Dr. Hasan Sadikin Hospital, Bandung. Patients received two creams, a combination of N-K and HQ, for split-face therapy, regardless of the sides of the face. All patients were followed up at 4 and 8 weeks. The clinical efficacy was assessed for skin lightening effects using a spectrophotometer (L* value) and the melasma area severity index (MASI). Adverse effects were assessed in all patients. Result: Both the N-K and HQ groups showed significant improvement in skin lightening and MASI scores on week 8 (p <0.05). There was no statistically significant difference in efficacy between the N-K and HQ groups (p >0.05). None of the patients in the N-K group complained of any adverse effects. Whereas in the HQ group, 23.07% presented with pruritus and mild erythema.